Correcting the type designations of Caryodaphnopsis baviensis and C. laotica (Lauraceae) - Sun, Tiantian; Wiersema, John; Yang, Yong (Phytotaxa, 2016)
There is confusion on the type collection of the name Nothaphoebe baviensis Lecomte, which had been cited either as Balansa 1445 or as Balansa 2445. We clarified this confusion by checking both collections. It turned out that the type is Balansa 2445, and Lecomte made an error in citation of the type in the protologue. Duplicates of the collection Balansa 1445 actually consist of a mixture including materials of Sapindaceae and Primulaceae. In addition, we found that the type collection of C. laotica Airy Shaw is Kerr 20893, not Kerr 20983, although the latter was cited in the protologue.